Perspectives on the commercial development of landing gear health monitoring systems - Phillips, Paul; Diston, Dominic; Starr, Andrew G. (Elsevier Science B.V., Amsterdam., 2011)
The development of health monitoring technologies for aerospace systems creates a number of challenges for the community of engineers and technical specialists as they seek to integrate the technology into well defined working practices. These challenges do not just extend to the technical, but require a number of commercial questions to be addressed. It is of vital importance, that there is a clearly identified need for aerospace health monitoring, both from a technological and commercial viewpoint. If these needs cannot be identified, then any attempt for marketing health monitoring as a necessary future technological requirement is doomed for failure. Health monitoring technology will need to either deliver significant cost saving benefits to the aircraft operator or demonstrated increases in aircraft safety. The objective of the paper is to provide an assessment of the commercial benefits and development of aircraft landing gear health monitoring. The commercial need and challenges for health monitoring systems are explored in this paper within the context of a changing aerospace maintenance industry and the role in which new systems technology will play. The key findings of the research study are that within the aerospace industry there is a desired paradigm shift within aircraft maintenance towards offering maintenance systems with predictive capabilities. This maintenance revolution will not just incorporate new technologies, but will result in aircraft maintenance packages tailored towards individual customer requirements. The study illustrates the state-of-the-art in health monitoring currently restricts aerospace integration and a number of key technical and commercial issues need to be addressed. Predictive health monitoring offers a variety of commercial benefits for maintenance providers, aircraft operators and manufacturers. However, in order for these benefits to be realised increased transparency in maintenance related information is required between these key players.
Keywords: Health monitoring, maintenance systems, landing gears, expert systems